Performance Enhancement of Phase Change Material PCM Thermal Energy Storage TES System Using Nanoparticles Additives: An Experimental Investigation - Ebtehal S. Hussain; Ihsan Y. Hussain (Tikrit Journal of Engineering Sciences)
Paraffin wax used as Phase Change Material (PCM) in Thermal Energy Storage (TES) is one possible solution to store excess energy as heat and release it when power generation is insufficient. However, the PCM had a disadvantage: low thermal conductivity. So, the researchers developed some methods for increasing it since PCM is critical for a wide range of technologies. The present study describes experimentally the investigation of the discharging process of paraffin wax dispersed with different concentrations (0.5% and 1% ) of gamma-alumina oxide (39.2 nm), titanium oxide (47.2 nm), and alpha-aluminum oxide (186 nm ), in TES system for different heat transfer fluid (HTF) velocities, i.e., 1 m/s,  3 m/s, and 5 m/s. The influence of nanoparticles on the PCM thermo-physical properties. The effect of discharging cycles on the stability of nanoparticles was also investigated. The findings indicated that the improvement in thermal distributions of paraffin mixed with 0.5% Tio2 was better than paraffin mixed with 0.5% gamma and 0.5% alpha at 1 m/s HTF velocity, while at 1% concentration, the gamma alumina was more effective than others in modifying the paraffine wax thermal behavior since the time-saving of it was 19.54% compared to pure paraffine. Repeating the thermal cycle negatively affected the PCM thermal behavior of the paraffine wax test with 0.5% alpha and 0.5% gamma at a velocity of 3 m/s. However, a relative enhancement of nearly 7.69% in solidification time for 0.5% Tio2 was found. At the same velocity (3 m/s), the reduction in solidification time of gamma alumina and Tio2 was 12.3% and 7.69%, respectively, with a mass fraction of 1%. The largest improvement of thermal conductivity of nano-PCM compared to pure wax was 56.80% at 1% Tio2. Furthermore, the improvement in heat transfer rate at 0.5% Tio2 and 1% gamma was 15.67% and 68.64%, respectively. The “negative” results of repeated thermal cycles indicated that the stability of nano-PCM remains a big challenge and requires a multidisciplinary approach to determine the behavior of nanomaterials in a dispersing medium.